REGRESSÃO ESPONTÂNEA DE CORDOMA APÓS COVID-19 - SILVA JÚNIOR, Luis Fernando Moura da (2021)
Understanding COVID-19 and its effects constantly brings new knowledge to the literature. The spontaneous remission of tumors is an event that has always sparked much interest in medical studies. In several cases in the literature, infectious events are mentioned concomitantly with the period of cancer remission. As a result, remission has been attributed to immunological events. In fact, it was these events that aroused interest in the study of oncological immunotherapies. Chordomas are usually slow-growing tumors, but are locally aggressive and associated with high rates of recurrence and mortality. Regarding said tumors, the literature has four published cases of regression, but none associated with COVID-19. Only one case of lymphoma had its remission associated with COVID-19. COVID-19 causes several changes in the functioning of the immune system, which may have a direct impact on the oncogenesis process and tumor immunoediting. The present paper aims to report a case of spontaneous regression of chordoma associated with SARS-COV-2 infection, compile the other cases in the literature available to establish common aspects, and propose possible mechanisms that could explain the association of these events.